Retirement party (Raton Range Raton, New Mexico, 1979)
Newspaper Article on Dr. Louis M. Pavletich and his retirement.
Master list item #: 15
File location is in the Raton File Cabinet
Keywords: Pavletich, Louis M; Pavletich, Helen; Local History; Biography; Life and Customs; Doctor; Retirement; Raton, New Mexico